Health Promotion Practices among Pregnant Women Attending Antenatal Clinics at a Tertiary Hospital in Nigeria - Ademuyiwa Adetona; Oluwaseyi Grace Adetona; Richard Dele Agbana; Tope Michael Ipinnimo; David Sylvanus Ekpo; Taofeek Adedayo Sanni (Wolters Kluwer Medknow Publications, 2024)
A cross-sectional study conducted in a semi-urban tertiary healthcare hospital in South western Nigeria to assess health promotion practices and associated sociodemographic factors among pregnant women attending antenatal clinics. A total of 220 pregnant women were studied. Results showed that 95.0% of the participants had good health promotion practices with physical activities having the lowest while spiritual values had the highest score. Moreover, age, religion, education, and occupation were significantly associated with health promotion practices among the pregnant women.